Developing Socio-Cultural Scaffolding Model to Elicit Learners’ Speech Production - Englishtina, Inti; Saleh, Mursid; Warsono, Warsono; Rukmini, Dwi (Universitas Negeri Semarang, 2016)
This study is concerned with developing scaffolding model to elicit bilingual kindergarten children’s English speech production. It is aimed at describing what the teachers need in eliciting their students’ speech production; how a scaffolding model should be developed to elicit the children’s speech production; and how effective is the scaffolding model in eliciting the children’s speech production.The participants of the study are teachers and students of kindergarten at Mondial SchoolSemarang. Preliminary research was conducted to describe what the teachers need to elicit their students’ speech production. Referring to the need analysis, a scaffolding model was developed to elicit the children’s speech production. To explain the effectiveness of the model a try out was carried out on the model developed. Based on the result of the try out, a final model was developed.The findings of the preliminary research suggest that Mondial School kindergarten teachers need a scaffolding model to elicit their students’ speech production. Referring to the findings a scaffolding model based on speech functions was developed. To explain the effectiveness of the model the developed initial model was tried out. Based on the result of the try out the final scaffolding model was developed.This study concludes that kindergarten teachers of Mondial School need a scaffolding model to elicit their children’s English speech production. Based on the need analysis, a Socio-cultural Scaffolding Model was developed. Referring to the result of the try out steps it is reasonable to argue that this product of Scaffolding Model is effective in eliciting English speech production of kindergarten students of Mondial School.